Prioritization of Erosion Hotspot Microwatersheds for Conservation Planning Using GIS and Remote Sensing Techniques in Antsokia-Gemiza District of North Shewa Zone, Ethiopia - Estifanos Lemma; Yitea Seneshaw Getahun; Tadesse Getachew (Applied and Environmental Soil Science)
Soil erosion is one of the most severe forms of land degradation, which has a wide range of adverse on-site and off-site impacts in the highlands of Ethiopia in general and in the study area in particular. The objective of this study was to estimate soil erosion, identify and prioritize erosion hotspot microwatersheds in Antsokia-Gemiza district. The Revised Universal Soil Loss Equation (RUSLE) was used to estimate the potential annual soil loss. Geographic Information System (GIS) and remote sensing techniques were used to delineate the microwatersheds, produce the spatial map of all parameters and outputs, and prioritize microwatersheds. Based on the analysis, the potential soil loss of the district ranges from 0 to 240 t·ha−1year−1 with a mean annual soil loss of 43.21 t·ha−1year−1. About 12442.86 ha (33.18%) of the district falls under low and moderate severity classes, and it has a total soil loss not exceeding 11 t·ha−1year−1 (which is an acceptable or tolerable range of soil loss). The rest of the land, which covers 25046.32 ha (66.82%) of the area, falls under high to extremely severe classes (which need prime attention), with soil loss amounts ranging from 11.01 to 240 t·ha−1year−1. For prioritization purposes, the estimated potential soil loss of the district was reclassified into 12 microwatersheds. Based on the amount of soil loss across each microwatershed, MW10, MW9, and MW11 ranked 1st, 2nd, and 3rd with a percentage of 96.3%, 94.36%, and 89.28%, respectively. On the other hand, the total area covered by the existing soil and water conservation practices in the district was 5606.10 ha, of which 3808.06 ha was covered by physical conservation measures, 1305.67 ha of the area was covered by biological conservation measures and 492.37 ha was covered by area closure. Most of the existing soil and water conservation measures were implemented under high to extremely severe erosion classes. The hotspot microwatersheds with higher severity percentages will get higher priority for soil and water conservation intervention. Hence, the integrated results will provide useful information for the decision-making process concerning the erosion susceptibility of microwatersheds. Besides, GIS and remote sensing approaches in the identification and prioritization of erosion hotspot microwatersheds using RUSLE parameters are found to be more appropriate.